(untitled) (Comunicação & Inovação, 2022)
This article on proximity radio journalism, in the state of Mato Grosso do Sul, aims to understand to what extent the news coverage dedicated to the Covid-19 pandemic resulted in changes in the productive routines of six stations located in the capital and in interior municipalities. From semi-structured interviews with sound stations representatives, it is concluded that they have been dedicated, although at different levels of importance, to counteract the informational disorder of spreading false content related to the Covid-19 pandemic by resorting to fact-checking agencies, traditional news sites and institutional sources at the local level.